2018
DOI: 10.1016/j.colsurfb.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing clot properties through fibrin-specific self-cross-linked PEG side-chain microgels

Abstract: Excessive bleeding and resulting complications are a major cause of death in both trauma and surgical settings. Recently, there have been a number of investigations into the design of synthetic hemostatic agents with platelet-mimicking activity to effectively treat patients suffering from severe hemorrhage. We developed platelet-like particles from microgels composed of polymers carrying polyethylene glycol (PEG) side-chains and fibrin-targeting single domain variable fragment antibodies (PEG-PLPs). Comparable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…65 Platelet-like microparticles have been developed that can stiffen a clot, induce retraction, and decrease susceptibility to fibrinolysis. 66,67 Perhaps the best-developed, a platelet analogue named Synthoplate (Haima Therapeutics) has shown promise. SynthoPlates are liposomes decorated with ligands that bind VWF, collagen, and fibrin, which allow them to recapitulate the binding properties of activated platelets.…”
Section: Novel Therapeutic Approaches To Platelet Dysfunctionmentioning
confidence: 99%
“…65 Platelet-like microparticles have been developed that can stiffen a clot, induce retraction, and decrease susceptibility to fibrinolysis. 66,67 Perhaps the best-developed, a platelet analogue named Synthoplate (Haima Therapeutics) has shown promise. SynthoPlates are liposomes decorated with ligands that bind VWF, collagen, and fibrin, which allow them to recapitulate the binding properties of activated platelets.…”
Section: Novel Therapeutic Approaches To Platelet Dysfunctionmentioning
confidence: 99%
“…Network permeability can be quantified using pressure-driven systems that examine fluid flow through a porous medium, such as a fibrin clot. [22][23][24] Although an indirect measure of pore size, this form of analysis provides insights into the porosity of fibrin clots, which can be an indicator for the degree of clot density and fibrinolysis resistance. Finally, mechanically based techniques are commonly used to analyze clot structure.…”
mentioning
confidence: 99%
“…Welsch et al reported different platelet-like particles carrying polyethylene glycol side chains and fibrintargeting single-domain variable fragment antibodies [125]. In vitro studies showed that the platelet-like particles were comparable to natural platelets with regards to enhancing the fibrin network formation through strong adhesion to the emerging fibrin clot and physical, noncovalent crosslinking of nascent fibrin fibers.…”
Section: Synthetic Plateletsmentioning
confidence: 99%